Islam Based Managerial Strategies for Employee Welfare: The Role of Islamic Work Ethics and Islamic CSR in the Virtual Work Environment of Madrasahs (International Journal of Education and Literature, 2025)
This study aims to analyze Islamic-based managerial strategies in improving employee welfare in madrasahs that implement remote working systems. In the context of virtual work, emerging challenges include increased burnout risk and decreased employee engagement. Therefore, this study proposes the application of Islamic Work Ethics (IWE) and Corporate Social Responsibility (CSR) Islam as approaches to address these issues. The research method used is descriptive with a literature review approach, analyzing relevant theories and the application of Islamic principles in employee welfare management in madrasah environments. The findings indicate that integrating Islamic values into employee welfare management can reduce burnout and enhance employee engagement. The implications of this study emphasize the importance of madrasahs adopting Islamic-based managerial models, which consider not only material welfare but also the spiritual and social well-being of employees, to create a healthy and productive work environment.